The Significance of the Orientation on the Overall buildings Thermal Performance-Case Study in Australia. (October 2018) - Albatayneh, Aiman; Alterman, Dariusz; Page, Adrian; Moghtaderi, Behdad
Abstract: Containing and then reducing greenhouse gases (GHG) emissions required designing energy efficient buildings which save energy and emit less GHG. Orientation has an impact on the building overall thermal performance and designing heating and cooling to reach occupants thermal comfort. Correct orientation is a low cost option to improve occupant's thermal comfort and decrease cooling and heating energy. An appropriate building orientation will allow the desirable winter sun to enter the building and allow ventilation in summer by facing the summer wind stream. In this paper a building module in Newcastle area, Australia will be assessed to find the effect of the building orientation and wind speed and direction on the overall thermal performance. It was found that the northern wall (windows side) of the Insulated cavity Brick (InsCB) module consistently provided the most heat to the room through the window which allows the sun in winter to enter the building and heat it up and avoid main wind stream.